Towards the effectiveness of communication in adopting virtual team for software development - Mohabuth, Abdool Qaiyum; Nankoo, Bibi Neehad (International Journal of Engineering and Computer Science, 2021)
: Advancement in technology particularly the development of smart application has caused a paradigm shift in software development. Teams for developing software do not need to be physically present at all times. Members of development teams may be at remote sites but still communicate with each other. Technology has enabled the creation of virtual teams. While technology put at the disposal of software development teams a range of devices for supporting their communication interaction, members still face many challenges in terms of time difference, language barriers and cultural diversification. Ineffective communication among team members lead to delays in software development and contribute much to make project failures. The primary focus of this research is to identify how communication in virtual teams may become efficient. A survey is carried to assess the factors which affect communication in virtual teams. Different team sizes are considered and their relevance and differences in communication interaction are studied. More in-depth data are extracted for this research by interviewing potential members of virtual teams who work and interact from remote sites. The factors which influence communication interaction is finally established which help in successfully managing virtual team projects